New York Heart Association class change on heart failure patients with implantable devices: does it matters?. (14th October 2021) - Duarte, F; Barradas, M.I; Oliveira, L; Serena, C; Dourado, R; Fontes, A; Monteiro, A; Machado, C; Santos, E; Pelicano, N; Tavares, A; Pacheco, M; et al.
Abstract: Background: Chronic heart failure (CHF) is a pathology with high prevalence and an important cause of morbidity and mortality. Benefits of implantable devices have been demonstrated in selected groups of patients with benefits on symptoms and heart failure hospitalization. Purpose: To determine the clinical impact of New York Heart Association class change (NYHA) in patients with CHF and Cardiac Implantable Electric Devices (CIEDs). Methods: We retrospectively enrolled 178 consecutive patients with CHF and CIEDs between November 2003 and January 2021, during a follow-up period of 51±43, 9 months. Patients demographic characteristic and NYHA class change impact on occurrence of arrhythmic events, heart failure hospitalization (HFH) or long-term admission in an emergency department were assessed. Patients with NYHA class change were considered responders to therapy. Results: Out of 178 patients enrolled in this study, sixty-seven (37, 6%) had a reduction ≥1 in NYHA functional class and in this group, 61 patients (91, 0%) had a cardiac resynchronization therapy (CRT) and 9% had an implantable cardioverter defibrillator. Mean age 68±11, 3 years, 44 (65, 7%) patients were male, 33 (49, 2%) were in NYHA class II, 30 (44, 8%) NYHA class III and 4 (6%) NYHA class IV. Mean QRS width 129, 9±63, 1 ms before CIEDs. Fifty-eight patients (86, 6%) had an improvement in one NYHA functional class and 9 patients (13, 4%) in two NYHA functional class. Fourty NYHA responders patients (59, 7%) had paroxistic or permanent atrial fibrillation and 31, 9% had an epicardial coronary artery disease, that was a negative predictor of NYHA response (p=0, 012). A total of 35 (19, 7%) enrolled patients experience non-sustained ventricular tachycardia (NSVT) and 74, 3% were non-responders (p=0, 019). There was fifteen and twenty HFH at 2 and 5 years of follow-up, respectively, and we observed that an improvement in NYHA class was associated with a reduction in HFH at 2 years of follow-up (p=0, 043; OR 0, 029, 95% CI 0, 050–1, 06) and 5 years of follow-up (p 0, 027, OR 0, 252; 95% CI 0, 069 – 0, 915). Emergency department (ED) admission related to HF decompensations was significantly reduced at 2 years of follow-up (p=0, 035, OR 0, 22, 95% CI 0, 048 – 1, 0) and at 5 years of follow-up (p=0, 001, OR 0, 15, 95% CI 0, 044 – 0, 55). There was no difference on cardiovascular or all-cause mortality. Conclusion: CHF patients with CIEDs and improving on NYHA class have less NSVT episodes, HFH and HF decompensations with ED admission, both at 2 and 5 years of follow-up. Funding Acknowledgement: Type of funding sources: None.